Comparative Study in Formal Structures, Style and Animal Species in Persian and Chinese Gabbeh Rugs - iman zakariaee kermani; zahra kargar (مجله مطالعات ایرانی, 2023)
Lion Gabbeh which shows a wide range of aesthetic and cultural-artistic principles of Iranian carpets that among them, the Ghashghaei pieces of the Fars province can be considered as an important group. The Lion Gabbeh weavers are very deep and ancient legacy of traditional heritage who are closely related to the rich Iranian culture. The tradition of weaving Lion Gabbeh does not belong only to Iranians, but a wide range of East Asian weavers, especially Chinese weavers, have created valuable samples of such hand-knits. This important cultural similarity between the two domains of Iranian and Chinese civilization is the basis of the most important goal of this research, which is to compare the Chinese and Iranian Fars Lion Gabbeh, in order to recognize the stylistic differences of each of them, the relations of design and its role as well as the fields of formation of these relations are discussed. In this regard, the main question arises, that what are the bipartite relationships in the form structures, style and animal species of the Fars and Chinese Lion Gabbeh?the selection of these samples in a targeted manner is an indicator sample and the required information and data have been collected in the form of documents. One of the most important findings of this research is the rooted role of Lion in the art of Gabbeh weaving in two regions, but the history of symbolic function concept of Lion in Iranian culture has a longer history.